The effect of tranexamic acid on blood coagulation in total hip replacement arthroplasty: rotational thromboelastographic (ROTEM®) analysis. (12th November 2015) - Na, H. S.; Shin, H. J.; Lee, Y. J.; Kim, J. H.; Koo, K. H.; Do, S. H.
Summary: We evaluated changes in rotational thromboelastometry (ROTEM ® ) parameters and clinical outcomes in patients undergoing total hip replacement arthroplasty, with concomitant infusions of tranexamic acid and of 6% hydroxyethyl starch 130/0.4. Fifty‐five patients were randomly assigned to either the tranexamic acid (n = 29) or the control (n = 26) group. Hydroxyethyl starch was administered in the range of 10–15 ml.kg −1 during the operation in both groups. In the control group, the clot formation time and maximum clot firmness of APTEM showed significant differences when compared with those of EXTEM at one hour postoperatively, suggestive of fibrinolysis. In the tranexamic acid group, there was no significant difference between each postoperative EXTEM and APTEM parameter. In the tranexamic acid and control group, postoperative blood loss was 308 ml (210–420 [106–745]) and 488 ml (375–620 [170–910], p = 0.002), respectively, and total blood loss was 1168 ml (922–1470 [663–2107]) and 1563 ml (1276–1708 [887–1494], p = 0.003). Haemoglobin concentration was higher in the tranexamic acid group on the second postoperative day (10.5 (9.4‐12.1 [7.9‐14.0]) vs. 9.6 (8.9‐10.5[7.3‐16.0]) g.dl −1, p = 0.027). In patients undergoing total hip replacement arthroplasty, postoperative fibrinolysis aggravated by hydroxyethyl starch was attenuated by co‐administration of 10 mg.kg −1 tranexamic acid, which may have led to less postoperative blood loss.